Small states in the global politics of development - Payne, Anthony (2004)
Looks at the global politics of finance, trade and the environment. Concludes that small states have been largely unsuccessful in asserting their own interests in global politics, and that vulnerabilities rather than opportunities are the most striking consequence of smallness in global politics.